Constructing Indonesian Religious Pluralism: The Role of Nahdlatul Ulama in Countering Violent Religious Extremism (JOURNAL OF INDONESIAN ISLAM, 2021)
This paper explores the role of the Nahdlatul Ulama (NU), the largest Muslim organisation in Indonesia, in advocating and practicing religious pluralism. It examines the organisation’s commitment to fostering religious pluralism and the institutionalisation of the principle of religious pluralism by interviewing and observing a number of NU administrators and/or activists from the national to the village level, and by reviewing official documents of the NU and articles in media published in East Java and Central Java. The article argues that the NU’s commitment to fostering religious pluralism develops through the organisation’s denunciation of various forms of religious violence and through mainstreaming moderate Islam. The article also contends that the NU’s notion of pluralism and its practices are not monolithic for there has been a spectrum of pluralism within the NU, ranging from the communal to liberal types of tolerance.